PENGEMBANGAN SEDIAAN EMULGEL MENGANDUNG MINYAK BIJI ANGGUR (Vitis vinifera L.) DAN UJI AKTVITAS ANTILUKA TERHADAP TIKUS WISTAR JANTAN (Rattus norvegicus) - Sani Ega Priani; Indah Ayu Lestari; Fetri Lestari (Jurnal Ilmiah Ibnu Sina (JIIS): Ilmu Farmasi dan Kesehatan, 2019)
Grape seed oil has wound healing activity since contains compounds such as flavonoids, polyphenols, saponins and linoleic acid. The purpose of this study is formulate emulgel containing grape seed oil with good physical characteristic and observed the wound healing activities of the oil and formulated emulgel. The research was begin with grape seed oil characterization and required HLB determination. The emulgel was made using combination Tween 80 and Span 80 as emulgator and carbomer as gelling agent with variation of oil concentration (10%, 20% and 30%). The formulation then subjected to physical evaluations including organoleptic, pH, spreadability, viscosity and rheology, sterility, and stability tests. Wound healing activity test of selected formula was done on seven groups of male Wistar rats. The emulgel containing grape seed oil with HLB value 8, has good physical, sterility, and stability characteristics. In vivo activity test showed that emulgel containing 20% and 30% grape seed oil have wound healing activity that statistically different compared with control (P<0.05) and the activity was not statistically different with marketed product (P>0.05).